Type 2 diabetes individuals improve C-reactive protein levels after high-intensity weight lift training - De Sousa, R. A.L.; Azevedo, L. M. [UNESP]; Improta-Caria, A.; Freitas, D. A.; Leite, H. R.; Pardono, E. (Elsevier, 2021)
Aims: Type 2 diabetes (T2D) increases the risk of developing cardiovascular diseases (CVD). Physical exercise, such as weight lifting training (WLT), is a non-pharmacological tool that can be used to prevent or treat T2D and CVD. The objective of this study was to evaluate changes in C-reactive protein (CRP) after 4 weeks of high-intensity WLT in individuals with T2D. Methods: The sample was composed by 40 male volunteers, who were divided into 4 groups of 10 individuals each: control, individuals with T2D (D), healthy trained (HT), and individuals with T2D who trained (DT). One maximum repetition test (1RM) was performed to obtain the intense WLT load (80% of 1RM). Exercises were performed 3 times a week during 4 weeks. Statistical analysis was carried out using the Graph Pad Prism 7.0, and the level of significance was set at 5%. Results: Hs-CRP, a biomarker that predicts cardiovascular risk, was significantly lowered at DT group (P < 0.05). T2D individuals had improvement in hs-CRP through high-intensity WLT performed at 80% of 1RM for 4 weeks. Conclusions: High-intensity WLT decreases CRP levels after 4 weeks, and, therefore,inflammation is reduced in T2D individuals. Lifestyle modifications through physical exercise, specially WLT, can lower the risk of CVD and help managing T2D.
Un entraînement de musculation à haute intensité améliore la protéines C-reactive dans le diabète de type 2
Keywords: Cardiovascular disease; Diabetes; Health; Inflammation; Resistance training